Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

If any point (x1,y1) is the solution of the equation ax+by+c = 0 then point must satisfy the equation.

i.e. ax1+by1+c = 0

given that

point => (0,7/3)

equation => x+3y - 7 = 0

put the point in the equation

0 + 3*7/3 - 7 = 0

0 = 0

hence point (0,7/3) is the solution of the equation x+3y-7 = 0

i.e. ax1+by1+c = 0

given that

point => (0,7/3)

equation => x+3y - 7 = 0

put the point in the equation

0 + 3*7/3 - 7 = 0

0 = 0

hence point (0,7/3) is the solution of the equation x+3y-7 = 0

i.e., x=0 and y=7/3

now by substituting these values in the equation- x+3y=7 OR x+3y-7=0 we get:

0+3*7/3-7=0,i.e,7-7=0

hence,as it satisfies the given condition,it is a solution for the equation